Effects of Instructional Package on Achievement of Beginners in French in Selected Secondary Schools in Oranmiyan Local Government Area of Oyo state. - Amosu, Sewanu Ayodele (Obafemi Awolowo University, 2014)
The purpose of this study is to determine the effect of an instructional package on beginners of French. The package consisted of an audio-taped lesson synchronized with a set of fourteen slides on a French concept - Time.